Makna Komunikasi Orangtua dan Anak dalam Film Animasi - Salma Luthfia Adriana; Moh. Subur Drajat (Bandung Conference Series: Public Relations, 2023)
Abstract. Film is a form of audiovisual work that is arranged so as to form a story that can be enjoyed and becomes a medium of communication through symbols and message systems. Film is a field of study that is relevant for semiotic analysis, because it is built with many diverse signs and works together to achieve the desired effect. In the process of communication, film can be used as a mass medium to convey messages through signs that form meaning. "Turning Red" is one of the animated films produced by two large companies, Pixar and Walt Disney. It tells the story of a Chinese-American girl who inherits knowledge from her mother so that she can turn into a big red panda. The theme is about family culture, mother and child relationship, parental domination, adolescent emotional state, and privacy in Asian parenting. The purpose of this study is to find out the signs in the film that are in line with Roland Barthes' theory, namely denotative meaning, connotative meaning and myth and are associated with the meaning of parent-child communication. The results of this study reveal the denotative, connotative, and mythical meanings in the communication between parents and children in the film. The analysis was carried out on 10 relevant scenes and dialogues. The denotative meaning is the literal meaning that can be felt and seen in the flow of the scene under study. Denotation as meaning that can be seen literally, connotation through allegories and myths depicts themes related to Asian culture, such as heritage, protection of family, ancestors or ancestors and upbringing. Abstrak. Film merupakan bentuk karya audiovisual yang disusun sehingga membentuk sebuah cerita yang dapat dinikmati dan menjadi media komunikasi melalui simbol dan sistem pesan. Film merupakan bidang kajian yang relevan bagi analisis semiotika, karena dibangun dengan banyak tanda yang beragam dan bekerja sama dalam mencapai efek yang diinginkan. Dalam proses komunikasi, film dapat dimanfaatkan sebagai media massa untuk menyampaikan pesan melalui tanda-tanda yang membentuk makna. “Turning Red” adalah salah satu film animasi garapan dua perusahaan besar, Pixar dan Walt Disney. Bercerita tentang seorang gadis keturunan amerika-tionghoa yang mewarisi ilmu dari ibunya sehingga ia bisa berubah menjadi panda merah besar. Mengangkat tema tentang budaya keluarga, hubungan ibu dan anak, dominasi orang tua, kondisi emosional remaja, dan privasi dalam pola asuh Asia. Tujuan penelitian ini untuk mengetahui tanda-tanda dalam film yang sejalan dengan teori Roland Barthes yaitu makna denotasi, makna konotasi dan mitos serta dikaitkan dengan makna komunikasi orangtua dan anak. Hasil dari penelitian ini mengungkap makna denotatif, konotatif, dan mitos dalam komunikasi orangtua dan anak dalam film tersebut. Analisis dilakukan pada 10 adegan dan dialog yang relavan. Makna denotasi adalah makna literal yang dapat dirasakan dan dilihat dalam alur scene yang diteliti. Denotasi sebagai makna yang dapat dilihat secara literal, konotasi melalui kiasan dan mitos menggambarkan tema-tema yang terkait dengan budaya Asia, seperti warisan, perlindungan keluarga, nenek moyang atau leluhur dan pola asuh.